Soft System Methodology Approach: Case Study of Renewable Energy Development of Wood Pellets as an Implementation of a Circular Economy - Dino Rimantho (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa dan Inovasi, 2024)
The development of wood pellets as a sustainable energy source derived from biomass waste has not significantly increased over the past few decades, despite a rise in demand for and sales of its products worldwide. Several variables contribute to the intricate issue of creating wood pellets from biomass waste as a renewable energy source, including the roles and responsibilities of various stakeholders, including the government, financial institutions, academia, the manufacturing sector, and non-governmental organizations. This article uses a waste management model that employs the Soft System Methodology (SSM) approach to assess the challenge of producing wood pellets from biomass waste as a renewable energy source and possible solutions. Data and information on the development of wood pellets as a renewable energy source derived from biomass waste were acquired through a literature review and in-depth interviews with specialists. The study’s findings demonstrate that using the SSM technique leads to a conceptual model that depicts the interactions between sub-elements to enhance the development of wood pellets as a biomass waste-derived renewable energy source. This concept was developed to lessen any adverse effects and enhance the processing of biomass waste. The success of goals is determined by the importance of each actor’s role and the collaboration of other actors, including local, national, and corporate governments. The Ministry of Environment and Forestry is the primary stakeholder and has a say in policy and program formulation. The Ministry of Industry, Energy and Mineral Resources, financial institutions, and other relevant organizations can help with this effort.